Liquid Chitosan from Corbula faba Hinds on Soil Transmitted Helminth (STH) in Pakcoy (Brassica chinensis L.) - Diah Titik Mutiarawati (Humanistic Network for Science and Technology (HNST), 2022)
Worms are a health problem that is still commonly found in developing countries. One of the causes of helminthiasis is Soil-Transmitted Helminth (STH). The worms that cause worm problems are Ascaris lumbricoides, Trichuris trichiura, Hookworm (Necator americanus and Ancylostoma duodenale). Chitosan has been discovered to have a quality positively charged polycationic, leading to changes in cell permeability. Chitosan can be found in the framework of Crustacea sp., such as white mussel shell. The purpose of this research was to determine the effectiveness of liquid chitosan from white mussel shells (Corbula faba Hinds) against Soil-Transmitted Helminth on Pakcoy (Brassica chinensis L.). The research results at a concentration of 2% on average worm larvae death time of 5.25 minutes, 1.5% concentration on average worm death time of 5.15 minutes, the concentration of 1% and 0.5% did not occur death of worm larvae. There is a significant difference in the exposure of liquid chitosan from white shell to death time of worm larvae. These results show that the liquid chitosan from white mussel shell to Soil-Transmitted Helminth on mustard meat is effective at a concentration of 1.5% with an average death time of 5.15 minutes. Keywords: Soil-Transmitted Helminth; chitosan; Corbula faba hinds